2012
DOI: 10.1016/j.jep.2012.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive, anti-inflammatory and wound healing features in animal models treated with a semisolid herbal medicine based on Aleurites moluccana L. Willd. Euforbiaceae standardized leaf extract

Abstract: The MSDP followed by HPLC-UV analytical method was appropriate for the quality control of the topical phytomedicine based on A. moluccana. The formulation developed at 0.5 and 1.0% of A. moluccana dried extract proved to be effective as an analgesic, anti-inflammatory and wound healing in the pre-clinical studies, which is in agreement with the ethnopharmacological data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 38 publications
0
15
0
5
Order By: Relevance
“…In fact, the resultsobtained shown that after croton oil administration in animals pretreated with A. moluccana extract the neutrophil migration was significantly reduced (41.50±9.30%, Figure 3). Quintão et al (2012) have also demonstrated that the treatment with A. moluccanadried extract, using oral administration route, was capable of drastically reducing the neutrophil migration induced by intraplantar injection of carrageenan. As mentioned before, the neutrophil migration depends on the production and release of chemokines.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…In fact, the resultsobtained shown that after croton oil administration in animals pretreated with A. moluccana extract the neutrophil migration was significantly reduced (41.50±9.30%, Figure 3). Quintão et al (2012) have also demonstrated that the treatment with A. moluccanadried extract, using oral administration route, was capable of drastically reducing the neutrophil migration induced by intraplantar injection of carrageenan. As mentioned before, the neutrophil migration depends on the production and release of chemokines.…”
Section: Resultsmentioning
confidence: 88%
“…The animals pre-treated with the semisolid containing the plant extract or dexamethasone, the drug used as positive control, was able to significantly reduce the edema with inhibition values of 35.77±7.35% and 97.69±2.30%, respectively. Cesca et al (2012) have demonstrated that a semisolid of A. moluccana (1%) significantly prevented the ear thickness increase (64.80±6.20%) when compared with the vehicle. It is important to mention that the semisolid composition previously used by the author was different, what could justify the difference between the achived inhibitions.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Medicinal plants have been identified as a safe and effective alternative for the treatment of dermatological inflammatory diseases, replacing conventional drugs such as corticosteroids and nonsteroidal anti-inflammatory drugs (Bralley et al 2008;Maldini et al 2009;Cesca et al 2012). In this study, we identified polar compounds in S. trilobata hydroethanolic extract and also developed a new topical phytomedicine based on KA content with significant anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…A. mollucanna has also been found to possess antiviral [33] and antimicrobial properties [34] demonstrating how the presence of multiple active compounds in plant extracts can have several benefits to patients. Due to this historical link between A. mullucanna and anti-nociceptive and antiinflammatory therapies, A. mullucanna extracts have been used to produce analgesic and anti-inflammatory phytomedicines [35,36]. The major focus of this work was on the wound healing effects of A. mollucanna extracts, although the use of this plant in traditional remedies for asthma suggests that there is a possibility for the active compounds of A. mullucanna to be adapted to produce a phytomedicine for asthma and its related symptoms.…”
Section: Plant-derived Therapies For Asthmamentioning
confidence: 99%